Economic survey of Burma 1960 : presented in Parliament by the Hon'ble Minister for Finance and Revenue, August 19, 1960 (Rangoon : Superintendent, Govt. Print. and Stationery, 1960)
The book examines the economic activities in Burma from 1959-1960.
usc 11/04/2019
Ref.
Keywords: Economic history; Economic conditions; Burma